Wild edible plants traditionally collected and used in southern Yemen - Mohamed Al-Fatimi (BMC, 2021)
Abstract Background The local wild edible plants (WEPs) are still used traditionally in the rural communities in Yemen, but this traditional knowledge is still undocumented and has been never reported before. Therefore, this study is the first ethnobotanical survey on WEPs conducted in Yemen. Methods The study is based on two field surveys made in two periods 1988-1992 and 2014-2016 to document the wild plants used as edible by local indigenous peoples in 23 districts belonged to five governorates, in southern Yemen. Information data were collected by oral face-to-face interviews from 250 informants. Citations numbers were calculated for each species. Results A total of 58 plant species belonged to 37 genera and 21 families are reported as wild edible plants consumed in southern Yemen. Apocynaceae was the dominant plant family with 18 species followed by Asteraceae (6) and Malvaceae (5). The most widely used edible parts are stem, leaf and fruit with more than 17 species for each. Herbs were reported as the most important sources (31 species), followed by shrubs (16) and trees (9). Most of reported wild edibles (48 species parts) are consumed in raw form; only 12 of them are cooked. Seven wild edible plants were collected in dry season, 16 species throughout the year and 38 in rainy season. In this study, 58 wild plants were reported for the first time as food in Yemen. Comparing the southern Yemeni findings to those from other world countries, 12 of them are new WEPs eaten only in southern Yemen, while 46 species are shared in the use in different world countries practically in East Africa and Arab countries. Conclusions The results data reflect the strong relationship between the local peoples and the local WEPs as potential sources insure food security. The traditional use of these WEPs is attributed to food shortage, nutritional values and local cultural tradition. The study is of great importance in preserving the traditional and knowledge heritage from being lost due to the risks of time, war and immigration.